Street art as a way to enhance the vitality of Uurban public spaces: Inspiration based on the experience of Taipei - Peng, Zhang; Wei, Dong (International Planning History Society Proceedings, 2018)
Street art is a unique artistic behavior that takes place in the urban public space. Its uniqueness is not only manifested in the form of immediacy, participation, and mobility, but also has a great value to enhance space dynamism, increase human interaction, and shaping the spirit of place. In most Chinese cities, street art is often equated with "fraud", which not only hampers the development of street art, but also hinders the promotion of vitality of public space, for a livable and lively city, the public space should not be merely a purely physical space, but should be the sum of the spirit of the place and the vitality of the space. The research question of this paper is: how to reduce the external negative effects of street art and actively shape and regenerate the vitality of urban public space? Research based on literature review and the summary, first of all, review and define the concept of "street art", and carries on the classification, it is believed that street art can change from "urban problem" to "urban landscape", then, the relationship between "street art" and "urban public space vitality" is discussed, performance analysis found a busker behavior can not only enhance the vitality of the public space (one-way intervention), also can attract audience participation, through the interaction with the audience to arouse public space activity (two-way intervention). And then from the perspectives of government, NGO and ordinary citizens, multi-dimensional detailed analysis the art management experience on the streets of Taipei, found that through the government management, system design, the multi-agent organization and the public participation to cultivate a variety of means such as, the urban public space of street art promotion activity provides effective guarantee system and management, and reduce the street art of the outer space of the city has negative effects. Based on this, the paper puts forward the spatial layout pattern of “centralized and decentralized complementarity”, the behavioral restraint mechanism of “rigidity and elasticity”, and the multi-agent intervention management of “organization and self-organization”,“Planning for Positive Public Opinion and Strict Enforcement of Law Enforcement” and other planning strategies. This paper argues that, by using the experience of management of Taipei street artists, from space, organization, policy formulation, implementation and operation aspects improve mainland China the level of city governance, with a view to providing references for the regeneration and shaping of the vitality of urban public space in China, and to provide a useful reference for the management of street artists.